Proof load testing method by AASHTO and suggestions for improvement - ICASP14; de Vries, Rein; Lantsoght, Eva O.L.; Steenbergen, Raphaël; Naaktgeboren, Marius (My University, 2023)
Due to the aging of infrastructure, methods are explored by which the reliability of existing bridges and viaducts can be assessed. In case limited information of the structure is available or its condition is of concern, proof load testing may be used to demonstrate sufficient load-carrying capacity. Proof load tests in the USA are typically performed using the Manual for Bridge Evaluation (MBE) published by AASHTO. The proof load is expressed by the regular live-load model magnified by the target proof load factor. The level of reliability obtained using the target proof load factor is not explicitly stated in the MBE, but is of particular interest. In this article relevant background documents are investigated to uncover the underlying calculations, assumptions and input data. Current challenges in proof load testing are described in which the consideration of time-dependence, stop criteria, available information and system-level assessment are highlighted. Subsequently, improvements to the MBE proof load testing background are suggested. An example calculation using traffic data from the Netherlands shows that the HL93 load model and Eurocode LM1 provide a reasonably constant proof load factor with span length for bending and shear. However, the HS20 load model does not scale well with increasing span length. It is found that the magnitude of the target load as specified through the proof load factor is directly related to the desired level of reliability. Although the MBE proof load testing method is practical, several challenges remain.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED